2020
DOI: 10.1111/jre.12820
|View full text |Cite
|
Sign up to set email alerts
|

Association between TNF‐α G‐308A (rs1800629) polymorphism and susceptibility to chronic periodontitis and type 2 diabetes mellitus: A meta‐analysis

Abstract: Background and objective Although the association between tumor necrosis factor‐α (TNF‐α) G‐308A (rs1800629) polymorphism and chronic periodontitis (CP), chronic periodontitis with type 2 diabetes mellitus (DP) is assumed, results of this association have been contradictory. The aim of this study was to assess the relationship between rs1800629 polymorphism and CP/DP susceptibility. Methods We searched for studies on PubMed, Web of Science, MEDLINE, Chinese National Infrastructure, and WanFang databases. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…Single‐nucleotide polymorphisms of the human tumor necrosis factor‐alpha gene TNF‐α , such as rs1800629 (−308 promoter polymorphism; A/G), leads to increased expression of the inflammatory cytokine tumor necrosis factor‐alpha, and it has also been connected to autoimmune diseases, including rheumatoid arthritis. Recently, the TNF‐α rs1800629 polymorphism was also found to be significantly associated with periodontal diseases 15 …”
Section: Rheumatoid Arthritis In the Reflection Of Periodontitis?mentioning
confidence: 99%
“…Single‐nucleotide polymorphisms of the human tumor necrosis factor‐alpha gene TNF‐α , such as rs1800629 (−308 promoter polymorphism; A/G), leads to increased expression of the inflammatory cytokine tumor necrosis factor‐alpha, and it has also been connected to autoimmune diseases, including rheumatoid arthritis. Recently, the TNF‐α rs1800629 polymorphism was also found to be significantly associated with periodontal diseases 15 …”
Section: Rheumatoid Arthritis In the Reflection Of Periodontitis?mentioning
confidence: 99%
“…In total, these polymorphisms may modify the expression and production of IL-1 and TNFα, affect host immune response and susceptibility to inflammatory diseases. Previous studies demonstrated that TNFα G-308A [ 18 , 19 ], IL-1α C-889T [ 20 ] and IL-1β C+3954T [ 21 ] polymorphisms were associated with risk of chronic periodontitis. The association between these polymorphisms with susceptibility to implant failure, marginal bone loss and peri-implantitis have also been widely explored, which, however, yielded inconsistent results [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms may increase the risk of inflammatory disease varied by region and race/ethnicity ( 47 ). A recent study reported that in the Asian population, tumor necrosis factor (TNF)-α G-308A (rs1800629) polymorphism is linked with increased susceptibility to chronic periodontitis ( 48 ). Also, smokers are at least 50% more likely to develop periodontitis than non-smokers, with faster progression, severer deterioration, and poorer treating efficacy ( 49 , 50 ).…”
Section: Dysbiosis and Dysregulated Inflammation Drive Periodontitismentioning
confidence: 99%